Analysis and Control of Output Synchronization for Complex Dynamical Networks - Wang, Jin-Liang.; Wu, Huai-Ning.; Huang, Tingwen; Ren, Shun-Yan.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book introduces recent results on output synchronization of complex dynamical networks with single and multiple weights. It discusses novel research ideas and a number of definitions in complex dynamical networks, such as H-Infinity output synchronization, adaptive coupling weights, multiple weights, the relationship between output strict passivity and output synchronization. Furthermore, it methodically edits the research results previously published in various flagship journals and presents them in a unified form. The book is of interest to university researchers and graduate students in engineering and mathematics who wish to study output synchronization of complex dynamical networks.
Introduction -- Output Synchronization Criteria for Impulsive CDNs with Time-varying Delay -- Passivity and Output Synchronization of CDNs with Fixed and Adaptive Coupling Strength -- Analysis and Control of Output Synchronization in Directed and Undirected CDNs -- Output Synchronization in CNNs with and without External Disturbances -- Local and Global Exponential Output Synchronization of CDDNs -- Adaptive output synchronization of CDDNs with output coupling -- Pinning Synchronization of CDNs With Multi-Weights -- Analysis and Pinning Control for Output Synchronization and H-Infinity Output Synchronization of Multi-weighted Complex Networks.
Keywords: Control engineering; Dynamics; Nonlinear theories; Mathematical models; Control and Systems Theory; Applied Dynamical Systems; Mathematical Modeling and Industrial Mathematics